2021
DOI: 10.3389/fphys.2021.751239
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Adipocytes and Adipose Stem Cells in the Breast Tumor Microenvironment and Regenerative Medicine

Abstract: Obesity rates are climbing, representing a confounding and contributing factor to many disease states, including cancer. With respect to breast cancer, obesity plays a prominent role in the etiology of this disease, with certain subtypes such as triple-negative breast cancer having a strong correlation between obesity and poor outcomes. Therefore, it is critical to examine the obesity-related alterations to the normal stroma and the tumor microenvironment (TME). Adipocytes and adipose stem cells (ASCs) are maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…Interaction between tumor cells and TAMs is complicated and involved cytokines, metabolites and exosomes [43,44]. In addition to TAMs, fibroblasts, lymphocytes, adipose cells and dendritic cells are included in the cell components of TME, and have been demonstrated to promote tumor malignant progression [45][46][47][48]. In our study, we only focused on the chemokines CXCL5 derived from TAMs and illuminated its critical role in 5-FU-resistnace, without evaluating its role in the invasion, angiogenesis or metastasis of gastric cancer, future study should focus on the effect of other components of the TME on the malignant progression in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between tumor cells and TAMs is complicated and involved cytokines, metabolites and exosomes [43,44]. In addition to TAMs, fibroblasts, lymphocytes, adipose cells and dendritic cells are included in the cell components of TME, and have been demonstrated to promote tumor malignant progression [45][46][47][48]. In our study, we only focused on the chemokines CXCL5 derived from TAMs and illuminated its critical role in 5-FU-resistnace, without evaluating its role in the invasion, angiogenesis or metastasis of gastric cancer, future study should focus on the effect of other components of the TME on the malignant progression in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] On the other hand, recent studies have shown that ASCs, through their interactions with cancer and immune cells, may contribute to tumor progression. 39,55 In the present study, we isolated human ASCs derived from breast tissue. ASCs' cultures were characterized by the expression of the mesenchymal stem cell surface markers CD105, CD73, CD44, and CD90, while they exhibited decreased expression of the hematopoietic stem cell surface marker CD45.…”
Section: Discussionmentioning
confidence: 99%
“…The latter play a supportive role in the tissue as they provide energy, participate in hormonal regulation, are capable of multilineage differentiation and secrete cytokines involved in wound healing, tissue repair, and homeostasis 30–33 . On the other hand, recent studies have shown that ASCs, through their interactions with cancer and immune cells, may contribute to tumor progression 39,55 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations